SOME ASPECTS OF LABOR MIGRATION IN JIZZAKH REGION (Scientific journal of the Fergana State University, 2025)
This article examines labor migration, one of the main types of mechanical population movement, its relevance, and territorial structure. The primary focus is on the causes of labor migration, as well as its territorial and sectoral composition.